The Molecular and Genetic Characterization of Second Chromosome Balancers in Drosophila melanogaster. Issue 4 (1st April 2018) - Miller, Danny E; Cook, Kevin R; Hemenway, Elizabeth A; Fang, Vivienne; Miller, Angela L; Hales, Karen G; Hawley, R Scott
Abstract: Balancer chromosomes are multiply inverted and rearranged chromosomes used in Drosophila melanogaster for many tasks, such as maintaining mutant alleles in stock and complex stock construction. Balancers were created before molecular characterization of their breakpoints was possible, so the precise locations of many of these breakpoints are unknown. Here, we report or confirm the positions of the 14 euchromatic breakpoints on the 2 nd chromosome balancers SM1, SM5, CyO, and SM6a . This total includes three breakpoints involved in a complex rearrangement on SM5 that is associated with the duplication of two genomic regions. Unbiased sequencing of several balancers allowed us to identify stocks with incorrectly identified balancers as well as single and double crossover events that had occurred between 2 nd chromosome balancers and their homologs. The confirmed crossover events that we recovered were at least 2 Mb from the closest inversion breakpoint, consistent with observations from other balancer chromosomes. Balancer chromosomes differ from one another both by large tracts of sequence diversity generated by recombination and by small differences, such as single nucleotide polymorphisms (SNPs). Therefore, we also report loss-of-function mutations carried by these chromosomes and unique SNP and InDel polymorphisms present on only single balancers. These findings provide valuable information about the structure of commonly used 2 nd chromosome balancers and extend recent work examining the structure of X and 3 rd chromosome balancers. Finally, these observations provide new insights into how the sequences of individual balancers have diverged over time.